The Effect of Palm Sugar and Storage on Nutrient Content and Taste of Salted Duck’s Egg - Yenni Yusriani (Jurnal Teknologi dan Industri Pangan, 2004)
This research used 150 duck eggs age one as subject day. There were two factors analyzed here. The first was the amount of palm sugar which consisted of 25 grams, 50 grams, and 75 grams. The second factor were the storage duration which consisted of 3, 4, and 5 weeks. The nutrient content parameters measured were rates protein, fat and ash content. Sensory quality parameters measured were color and taste. The analysis showed that in processing/making salted duck egg, palm sugar addition influenced protein content significantly (Fc = 7,0 > Ftab = 4,5) fat content ( Fc 67,3 > Ftab= 8,7) and ash content (Fc = 64,6 > F tab = 8,7) very significantly. However, organoleptic test showed that palm sugar addition did not influenced color and taste of salted duck egg significantly. Storage duration influenced protein content significantly (Fc= 6,9 < f tab = 4,5), and fat content very significantly (Fc = 12,7 >F tab = 8,7) but did not significantly influenced ash content (Fc = 3,5 < Ftab = 4,46). Storage duration also influenced taste of salted duck egg, but did not for its color. The interaction of treatment between palm sugar addition and storage duration just influenced fat content of salted duck egg significantly. The salted duck egg made by addition 75 grams palm sugar and stored 5 weeks (A3B3) the highest content of fat. The salted duck’s eeg made by addition of 25 grams palm sugar and stored duration produced the salted duck’s egg with high content of fat and ash. Organoleptic test indicated that the panelis preferred the salted taste duck egg made by addition of palm sugar 25 grams and storaged for 3 weeks having reddish yellow color. Key words : Salted duck egg, palm sugar, strorage duration, nutrient content sensory quality